Eksistensi Sertifikat Elektronik dal¬am Kebijakan Menteri ATR/Kepala BPN terhadap Upaya Pencegahan Mafia Tanah - Sekarwangi, Bestari Prahastani Intan; Iranda, Resty (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the legal protection provided to electronic land certificate holders and the policy of the Minister of ATR/Head of BPN regarding the issuance of electronic documents in land registration activities. This research uses a normative legal research approach that combines descriptive analysis with certain research criteria. Based on research, the aim of the Minister of ATR/Head of BPN's policy regarding electronic certificates is First, to reduce land dispute problems such as land mafia tactics. Second, the Information and Electronic Transactions Law and Regulation of the Minister of ATR/Head of BPN Number 3 of 2023 concerning Issuance of Electronic Documents in Land Registration Activities in the Context of Amendments to Legislative Regulations provide legal protection to land certificate holders electronically. Legislation governing electronic certificates issued by the Minister of Agrarian Affairs and the Head of BPN Number 1 of 2021.